Construcción de un sistema de medición de porosidad por medio de comparación de cámaras de aire basado en las modificaciones propuestas por Philipe Leclaire y evaluación del mismo comparándolo con el método de saturación de poros con líquido basado en el principio de Arquímedes (2017)
Based on the need for the Colombian industry to develop alternative characterization methods for acoustic materials, a system for porosity measurement will be developed from the designs of Leo Beranek, the porosity will be obtained using this method and also by the missing mass method created by Gross & Panetton, after completing the measurements, a statistical analysis will be performed with the data acquired. The aim of this project is to develop a low cost porosity measurement system for a different range of materials. Furthermore, with the data obtained in this project and results of previous investigations the absorption of different materials will be simulated using Champoux-Allad model. Knowing that there were previous investigations in the institution aiming in a similar direction, this project is seen as a step closer to achiving a more reliable analytical estimation of absorption coefficients based on materials properties such as density, tortuosity, flow resisitivity and porosity.